(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Maternal and child health is a critical aspect of public health, focusing on the well-being of women during pregnancy, childbirth, and the postpartum period, as well as the health and development of infants, children, and adolescents. Public health nursing plays a vital role in improving outcomes in this area through various interventions. This article provides a comprehensive overview of the role of public health nurses in enhancing maternal and child health outcomes, including strategies, challenges, and success stories.